Development of clinical value unit method for calculating patient costs. (3rd June 2019) - Cyganska, Malgorzata; Cyganski, Piotr; Pyke, Chris
Abstract: The objective of the study was to develop the clinical value unit method of allocating indirect costs to patient costs using clinical factors. The method was tested to determine whether it is a more reliable alternative to using the length of stay and marginal mark‐up allocation method. The method developed used data from a Polish specialist hospital. The study involved 4, 026 patients grouped into nine diagnosis‐related groups (DRG). The study methodology involved a three stage approach: (a) identification of correlates of patient costs, (b) a comparison of the costs calculated using the clinical value unit method with the alternative methods: length of stay and marginal mark‐up methods, and (c) an estimation of the cost homogeneity of the DRGs. The study showed that length of stay cost allocation method may underestimate the proportion of indirect costs in patient costs for a short in‐patient stay and overestimate the cost for the patients with a long stay. The total costs estimated using the marginal mark‐up method were higher than those estimated with length of stay method. For most surgical procedures, the mean indirect costs are higher using clinical value unit method than when using length of stay or marginal mark‐up method. In all medical procedure cases, the mean indirect costs calculated using the clinical value unit method are in the range between marginal mark‐up and length of stay method. We also show that in all DRGs except one, that the coefficient of homogeneity for clinical value unit is higher than for length of stay or marginal mark‐up method. We conclude that the clinical value unit method of cost allocation is a more precise and reliable alternative than the other methods.